Pengaruh Tidak Langsung Penggunaan Alat Kontrasepsi terhadap Kejadian Stunting di Desa Oetutulu, Kabupaten Rote Ndao - Wahyudi Loe; Daniela L.A. Boeky; Cathrin W.D. Geghi (Yayasan Literasi Sains Indonesia, 2024)
Stunting is a disorder of child growth and development due to chronic malnutrition and recurrent infections, characterized by a child's length or height below the standard. Indirect causes of stunting include ineffective parenting, health services, food availability, economy, parental education, clean water sources and environmental sanitation. The use of contraceptives is also one of the indirect causes of stunting. In 2023, Northwest Rote Subdistrict experienced 338 incidents of stunting and Oetutulu Village experienced 51 prevalence of stunting caused by a lack of good pregnancy planning, so that the birth distance became too close. This research is an analytic survey research using cross-sectional method. The purpose of this study was to determine the effect of contraceptive use on the incidence of stunting in Oetutulu Village, Rote Ndao Regency. The results showed that there was a significant influence between knowledge (p=0,034) and attitude (p=0,025) of couples of childbearing age on the use of contraceptives. The use of contraceptives also affects the incidence of stunting in Oetutulu Village, Rote Ndao Regency. It is expected that the community of Oetutulu Village can better plan pregnancy programs and use contraceptives as an effort to reduce the incidence of stunting.